Effects of slope length on runoff from alfisols in Western Nigeria - Lal, R. (1983)
The effects of 5, 10, 15 and 20 m slope lengths were investigated on runoff for natural slope gradients of about 1, 5, 10 and 15%. These studies were conducted on field runoff plots on natural slopes and under natural rainfall conditions at Ibadan in western Nigeria. The runoff, based on individual rainfall events, was not significantly correlated with either of three erosivity indices (EI30, KE > 1, AIm) and only a maximum of 36% of variability in runoff could be attributed to rainfall erosivity. Runoff per unit area decreased with increase in slope length. The mean annual runoff was of the order of 100, 87, 80 and 69 for 1977 and 100, 66, 49 and 35 for 1978 for 5, 10, 15 and 20 m slope lengths, respectively. Regression analyses indicated that the annual runoff was related to slope length according to the regression equation W = 773 L−0−53, where W is annual runoff in mm and L is slope length in meters. When fitted to data from all plots on a given slope steepness, for individual years the numerical value of length exponent b ranged from 0.153 to −0.865.